LEARNING TO WRITE ANECDOTAL TEXTS BASED ON LOCAL WISDOM USING THE DISCOVERY LEARNING MODEL IN GRADE X OF SMTI BANDA ACEH VOCATIONAL SCHOOL - Kustina, Rika; Harfiandi, Harfiandi; Asyura, Reza (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to see the success of students' learning in writing anecdotal texts based on local wisdom in class X SMK SMTI Banda Aceh. This study uses a quantitative approach with an Experiment type. The population of this study used two classes, namely class X TMI B and TMI C. The sample was selected randomly and class X TMI B was selected as the experimental class and TMI C as the control class totaling 54 people. Data collection was carried out through tests. The data were analyzed using a one-tailed t-test (right side), to determine the success of students' learning in class X TMI B and C SMK SMTI Banda Aceh in understanding the anecdotal text material with the application of the discovery learning model. The t-test shows the t-value of the control class is |-16.605|>1.705 t table and the significance value (2-tailed) is 0.001 (p <0.05). And the t-value of the experimental group is |-23.844| > 1.705 t table and significance value (2-tailed) is 0.001 (p < 0.05). This means that there is an increase in student learning success in learning to write anecdotal texts based on local wisdom through the discovery learning model for class X SMK SMTI Banda Aceh.